2020
DOI: 10.1128/mbio.02764-19
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Sialoside and Protein Receptors in Coronavirus Infection

Abstract: Coronaviruses (CoVs) are common human and animal pathogens that can transmit zoonotically and cause severe respiratory disease syndromes. CoV infection requires spike proteins, which bind viruses to host cell receptors and catalyze virus-cell membrane fusion. Several CoV strains have spike proteins with two receptor-binding domains, an S1A that engages host sialic acids and an S1B that recognizes host transmembrane proteins. As this bivalent binding may enable broad zoonotic CoV infection, we aimed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 87 publications
(97 reference statements)
3
113
0
Order By: Relevance
“…The surgical face mask design has undergone review in a clinical setting and was found appropriate when fabricated with the printer type and materials specified. 23 Virus titers were determined by determining the TCID 50 in the cognate cell line as previously described 28,34,35 or by p24 ELISA (R&D Systems) for HIV-1. 29…”
Section: Methodsmentioning
confidence: 99%
“…The surgical face mask design has undergone review in a clinical setting and was found appropriate when fabricated with the printer type and materials specified. 23 Virus titers were determined by determining the TCID 50 in the cognate cell line as previously described 28,34,35 or by p24 ELISA (R&D Systems) for HIV-1. 29…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that dipeptidyl peptidase 4 (DPP4) is a functional receptor for the emerging human coronavirus via S-protein, as well as ACE2 [34]. The interaction between the virus and the host cell membrane allows for viral S-protein-directed cell-cell fusion, and the resultant spread of viral infections [35]. As another example relevant to drug repurposing and the ideal strategy for confronting COVID-19, the specific role of DPP4 on COVID-19 remains to be investigated.…”
Section: Dipeptidyl Peptidase 4 (Dpp4; Cd26)mentioning
confidence: 99%
“…The split luciferase fusion assay has been described before, with slight modifications 54 1 hour, before Rluc activity was determined using the Renilla Luciferase Assay System (Promega). Cells were kept on ice during all times post-cell lysis to eliminate DSP post-lysis complementation.…”
Section: Split Luciferase Fusion Assaymentioning
confidence: 99%